Analisis kesehatan Lembaga Perkreditan Desa (LPD) se-Kabupaten Badung - A.A Pt. Agung Mirah Purnama Sari; Ni Nyoman Sri Rahayu Damayanti; I Wayan Gde Yogiswara Darma Putra (MBR (Management and Business Review), 2021)
Lembaga Perkreditan Desa (LPD) was established to strengthen the socio-cultural and economic life of the Balinese indigenous people, its implementation is not subject to the central government, but refers to local policies. The purpose of the study was to analyze the health of the LPD in Badung Regency. This is a descriptive study with a quantitative approach, using secondary data from LPD financial statements for 2017-2019. During 2017–2019 LPDs in the healthy category experienced an increase of 1%, for the fairly healthy category it did not change, the less healthy category increased by 3%, and the unhealthy decreased by 4%. LPD health analysis was measured by CAEL analysis. In 2017, 2018, and 2019 respectively, there were 13, 12, and 9 unhealthy LPDs; 5, 10, and 8 are not healthy; 24, 21, and 24 are quite healthy; and 61, 60, and 62 in the healthy category.